Health behaviours reported by adults with congenital heart disease across 15 countries. (July 2020) - Holbein, Christina E; Peugh, James; Veldtman, Gruschen R; Apers, Silke; Luyckx, Koen; Kovacs, Adrienne H; Thomet, Corina; Budts, Werner; Enomoto, Junko; Sluman, Maayke A; Lu, Chun-Wei; Jackson, Jamie L; et al.
Background: Health behaviours are essential to maintain optimal health and reduce the risk of cardiovascular complications in adults with congenital heart disease. This study aimed to describe health behaviours in adults with congenital heart disease in 15 countries and to identify patient characteristics associated with optimal health behaviours in the international sample. Design: This was a cross-sectional observational study. Methods: Adults with congenital heart disease ( n = 4028, median age = 32 years, interquartile range 25–42 years) completed self-report measures as part of the Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease - International Study (APPROACH-IS). Participants reported on seven health behaviours using the Health Behaviors Scale-Congenital Heart Disease. Demographic and medical characteristics were assessed via medical chart review and self-report. Multivariate path analyses with inverse sampling weights were used to investigate study aims. Results: Health behaviour rates for the full sample were 10% binge drinking, 12% cigarette smoking, 6% recreational drug use, 72% annual dental visit, 69% twice daily tooth brushing, 27% daily dental flossing and 43% sport participation. Pairwise comparisons indicated that rates differed between countries. Rates of substance use behaviours were higher in younger, male participants. Optimal dental health behaviours were more common among older, female participants with higher educational attainment while sports participation was more frequent among participants who were younger, male, married, employed/students, with higher educational attainment, less complex anatomical defects and better functional status. Conclusions: Health behaviour rates vary by country. Predictors of health behaviours may reflect larger geographic trends. Our findings have implications for the development and implementation of programmes for the assessment and promotion of optimal health behaviours in adults with congenital heart disease.